2013
DOI: 10.13181/mji.v22i4.606
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand tobacco smoke in public venues in three Indonesian cities

Abstract: Abstrak AbstractBackground: The aim of this study was to measure secondhand tobacco (including kretek) smoke (SHS) concentrations in public places in Jakarta, Bogor, and Palembang before laws banning smoking in public spaces went into effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…As has been observed in Indonesia [20,21] and internationally [22,23,24], we found that non-enforcement of smoke-free laws fails to provide needed protection from SHS exposure for nonsmokers, including children. The PM 2.5 levels observed in this study were lower than those found in a 2009 convenience sample of 17 restaurants in Jakarta (~110 µg/m 3 ) [21] and in many similar venues sampled globally [16,25,26]. Nonetheless, extended exposure to the PM 2.5 levels observed in this study would be far in excess of the annual average standard of 10 µg/m 3 recommended by the WHO [17].…”
Section: Discussionsupporting
confidence: 62%
“…As has been observed in Indonesia [20,21] and internationally [22,23,24], we found that non-enforcement of smoke-free laws fails to provide needed protection from SHS exposure for nonsmokers, including children. The PM 2.5 levels observed in this study were lower than those found in a 2009 convenience sample of 17 restaurants in Jakarta (~110 µg/m 3 ) [21] and in many similar venues sampled globally [16,25,26]. Nonetheless, extended exposure to the PM 2.5 levels observed in this study would be far in excess of the annual average standard of 10 µg/m 3 recommended by the WHO [17].…”
Section: Discussionsupporting
confidence: 62%
“…Hal ini mengindikasikan bahwa tidak ada area khusus yang aman untuk perokok pasif, sehingga perlu didukung peraturan terkait bebas asap rokok di tempat-tempat umum. 6 Tingginya jumlah perokok aktif akan semakin meningkatkan risiko keterpaparan perokok pasif terhadap dampak lanjutan bagi kesehatan akibat menghirup asap rokok orang lain. Hal ini dapat diperburuk jika penegakan aturan KTR lemah dan atau kurangnya pemahaman masyarakat akan penerapan KTR.…”
Section: Pendahuluanunclassified
“…Studies of smoke-free policies show that there is a positive impact on the health of the entire population and a decrease in smoking prevalence numbers [3]. A cross-sectional study from three cities in Indonesia ( Jakarta, Palembang and Bogor) also found that there is urgency to implement a widespread, comprehensive, 100% smoke-free policy in Indonesia without exceptions for designated smoking areas [4]. The adoption of a smoke-free policy in Indonesia is a critical decision for protecting individuals from second-hand smoke and reducing the high rate of smokers.…”
Section: Introductionmentioning
confidence: 99%